2013
DOI: 10.1210/er.2012-1013
|View full text |Cite
|
Sign up to set email alerts
|

Familial Isolated Pituitary Adenomas (FIPA) and the Pituitary Adenoma Predisposition due to Mutations in the Aryl Hydrocarbon Receptor Interacting Protein (AIP) Gene

Abstract: Pituitary adenomas are one of the most frequent intracranial tumors and occur with a prevalence of approximately 1:1000 in the developed world. Pituitary adenomas have a serious disease burden, and their management involves neurosurgery, biological therapies, and radiotherapy. Early diagnosis of pituitary tumors while they are smaller may help increase cure rates. Few genetic predictors of pituitary adenoma development exist. Recent years have seen two separate, complimentary advances in inherited pituitary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
292
2
12

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 311 publications
(316 citation statements)
references
References 229 publications
(175 reference statements)
10
292
2
12
Order By: Relevance
“…These larger adenomas appearing at a younger age may indicate more aggressive tumor behavior. One reason for this increased growth might be molecular genetic factors, as this profile of larger adenomas in young patients is shared with AIP-mutation-related adenomas (Beckers et al 2013). In terms of somatic DNA alterations, GSP oncogeneactivating mutations are the most frequently encountered (Landis et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…These larger adenomas appearing at a younger age may indicate more aggressive tumor behavior. One reason for this increased growth might be molecular genetic factors, as this profile of larger adenomas in young patients is shared with AIP-mutation-related adenomas (Beckers et al 2013). In terms of somatic DNA alterations, GSP oncogeneactivating mutations are the most frequently encountered (Landis et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…At doses within the indicated range of about 2 mg per week, resistance to cabergoline treatment is rare. A recent multicenter study in 92 resistant prolactinomas reported that they comprised only about 3.4 % of prolactinomas overall, although this rate rose to 13 % in those with a genetic component to their tumorigenesis [21], such as AIP mutation [22,23]. Cabergoline has a long half-life and its potent D2 receptor affinity leads to a rapid and effective control of many prolactinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Phaeo/PGL have not been reported in patients with mutations in AIP (Beckers et al 2013, Hernández-Ramírez et al 2015. No pheo/PGL or mutations in pheo/PGLpredisposing genes have been identified in 23 families with AIP mutation negative familial isolated pituitary adenomas (Dénes et al 2015).…”
Section: Aryl Hydrocarbon Receptor-interacting Proteinmentioning
confidence: 99%